Distintos tipos de constantes en física y aprendizaje significativo de la disciplina - Colombo de Cudmani, L.; Salinas, Julia; Pesa de Danón, M. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
From teaching experience data, some problems referred to the learning of conceptuations of constants that appear in the relation between physical magnitudes, are delimited. Some significative problems are identified. Two general hypothesis and four derived hypothesis are formulated. In order to get more information some questionnaires are prepared. The students' answers are analysed in different groups. Some clues are identified trying to explain the observed behaviours. They are useful as a base for the proposal of teaching strategies.